Welcoming and mental health: professional challenge in the family health strategy - Débora Helena Iversen Sucigan; Vanessa Pellegrino Toledo; Ana Paula Rigon Francischetti Garcia (Universidade Federal do Ceará, 2012)
This exploratory and descriptive study aims to understand how nursing professionals from family health teams welcome mental health patients and their feelings towards this work. The research was accomplished at a primary health care unit in Campinas (SP). Two categories were acknowledged: the differences between welcoming and forwarding and: knowing oneself and the other: a possibility for welcoming. The discussion on the findings was mainly based on Rogers' reference framework. It was apprehended that welcoming was fundamentally characterized as a form of forwarding nursing professionals use. On the other hand, it was acknowledged that, when welcoming was successful and managed to solve problems, those professionals could use their empathetic skills, despite ignoring empathy as a method. This reveals what it really means to gain self-confidence and ability to value the patient's experience, leading to an improvement in that relation and greater production in health.